The Construction of American Pop Identity in the News Media Coverage of the Girl Group KATSEYE - Silvia Dini Azzahra; Khaerudin Imawan; Aghnia Dian Lestari (Pelopor Publikasi Akademika, 2026)
The influence of global popular culture and media has prompted debates over how American pop identity is constructed, circulated, and negotiated within the music industry. This study aims to examine how news media construct KATSEYE, a multicultural girl group created by HYBE and Geffen Records, as an American pop and global cultural icon. Employing a qualitative approach, this research applies Norman Fairclough’s three-dimensional Critical Discourse Analysis, which covers textual analysis, discursive practice, and sociocultural practice, complemented by Adorno and Horkheimer’s culture industry perspective. Data were purposively collected from news coverage published between June and August 2024, along with interviews with a Cosmopolitan editor and members of the KATSEYE fandom. The findings reveal that media narratives frame KATSEYE through labels such as “the biggest global girl group,” positioning the American market as a benchmark for global success. This framing reflects industrial collaboration, algorithmic distribution, cultural commodification, and the marketing of diversity and empowerment. Nevertheless, fandom audiences do not passively accept these discourses; instead, they negotiate them by emphasizing hybridity, authenticity, multicultural representation, personal connection, and artistic merit. The study concludes that KATSEYE’s American pop identity is neither fixed nor exclusively controlled by the industry but is continuously reconstructed through interactions among media institutions, entertainment corporations, digital platforms, and participatory global audiences.